Clinical research in the National Football League: The Player Scientific and Medical Research Protocol - Mack, C.; Matava, M.; Zeidler, K.; Sills, A.; Solomon, G. (Current Sports Medicine Reports, 2020)
Sport is an international obsession for many people. Ensur-ing that athletes can compete in as safe of an environment as possible is vital not only in terms of the players' individual health and the teams' success in competition but also serves as a point of public health impact and as an example to young athletes. Sports injury surveillance and player health research is an essential component of injury prevention, reduction, and ultimately, player wellness. The National Football League (NFL) has established a robust injury researchstructure across all facets of athlete health. Consistent with established ethical principles and good practice for medical research, the NFL and NFL Players Association (NFLPA) jointly developed a Player Scientific and Medical Research Protocol Approval Process (MRAP) through which NFL player electronic injury and illness data may be used for the purposes of observational and interventional research. MRAP was agreed to by the NFL and NFLPA as a side letter agreement to the 2011 NFL-NFLPA Collective Bargaining Agreement (CBA), dated January 26, 2015, and has been updated over time. This process provides oversight of the access, utilization, and management of NFL health data to: 1) ensure thatthe potential research is feasible, valuable, and methodologically sound; (2) protect the confidentiality interests of NFL players and assure that appropriate personal information is not released to the public; and 3) avoid the duplication of research efforts between the NFL's medical committees, with the overall goal of ensuring that the goals of the intended research are consistent with the interests of the patient (player) and institution (NFL).